It's not the how or the what but the who succeed by surrounding yourself with the best - Fernandez Araoz, Claudio (Boston Harvard Business Review Press, 2014)
Succeed by mastering the art of the who Why surround yourself with the best? Because it matters-in all aspects of life. In fact, in professional environments, getting people right-what global leadership authority Claudio Fernandez-Araoz calls "the art of great; who? decisions"-marks the difference between success and failure. To thrive, you need to identify those with the highest potential, get them in your corner and on your team, and help them grow. Yet surprisingly very few of us are able to meet that challenge. This series of short and engaging essays outlines the obstacles to great "who" decisions and offers solutions to address them in a systematic way. Drawing from several decades of experience in global executive search and talent development, as well as the latest management and psychology research, Fernandez-Araoz offers wisdom and practical advice to improve the choices we make about employees and mentors, business partners and friends, top corporate leaders and even elected officials. The personal stories and cutting-edge studies described in the book will help you understand both your own failings and the external forces commonly at play in staffing decisions. The author shares concrete recommendations on how to select the best people, bring out their strengths, foster collective greatness in the groups you?ve assembled, and create not only better organizations but also a better society. Starting with the cases of Amazon pioneer Jeff Bezos and Brazilian tycoon Roger Agnelli and continuing with individual and corporate examples from around the world, Fernandez-Araoz paints a vivid picture of what great "who" decisions look like and presents a fresh and commanding argument about why they matter more than ever today. "
includes index
Keywords: Personnel management